Evaluating the potential of agile branding: opportunities and challenges in the start-up context. - Pöhlmann, Michaela; De-las-Heras-Pedrosa, Carlos; Seitz, Jürgen; Jambrino-Maldonado, Carmen (Springer Nature, 2025)
The necessity for companies to adopt an agile brand management approach to maintain relevance and competitiveness in our dynamic and fast-moving world is a key finding of recent studies. Nevertheless, no study has yet investigated the potential and applicability of the concept of agile branding. Concurrently, start-ups are confronted with the challenge of high failure rates due to shortcomings in brand management. The necessity for start-ups to adopt innovative and dynamic brand strategies arises from the constant internal and external changes that characterise the start-up environment. Previous studies on brand management, by contrast, have mainly focussed on established companies. Given the affinity and need for agility observed in start-ups, agile branding appears to be particularly relevant for start-ups. This study aims to address two research gaps: firstly, to explore the potential of the concept of agile branding and, secondly, to expand academic research of branding practices tailored to start-ups to assist them in overcoming the specific brand management challenges they face. The study draws on an extensive and structured literature review, followed by qualitative semi-structured interviews with eleven experts and 18 start-ups, to discuss the opportunities and challenges of agile branding in the context of start-ups. The results were analysed from the perspective of the five dimensions of agile branding and the dynamic capabilities framework. Agile branding offers start-ups the opportunity to adapt swiftly to market changes, allocate resources efficiently, and reduce risk through data-driven decision-making.
Keywords: Marcas (Marketing); Nuevas empresas; Emprendedores; Comunicación empresarial; Agile branding; Startups; Entrepreneurship; Communication